2021
DOI: 10.1002/hyp.14090
|View full text |Cite
|
Sign up to set email alerts
|

Sap flow and plant water sources for typical vegetation in a subtropical humid karst area of southwest China

Abstract: Plant water use plays a crucial part in the soil-plant-atmosphere continuum. However, in karst regions, plants frequently suffer from water shortages due to low soil water storage capacity. Therefore, it is necessary to understand plant water consumption (as determined by sap flow) and seasonal variation of water sources to improve water management in karst catchments. In this study, thermal dissipation probes (TDP), calibrated using empirical equations, were used to measure the sap flow of three typical woody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 77 publications
2
10
0
Order By: Relevance
“…For different vegetation succession stages, the smallest ET is from cropland ( Zea mays + Brassica napus ), mainly result from that the planting density of Zea mays is smaller than that of grass to ensure high yield, and Brassica napus with high LAI grows in winter when PET is low (Figure S4 in Supporting Information ). While the secondary forest has the highest ET among all vegetation types, due to the large canopy and water uptake from the deep fractured bedrock (J. Y. Hu et al., 2021; Yang et al., 2014; Zeng et al., 2021). These variations of ET among vegetation types suggest that natural vegetation restoration increases ecosystem ET in the humid karst region, which is also similar to the findings in other non‐karst regions (Liu et al., 2013; Rohatyn et al., 2018; Twine et al., 2004; Zhang et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For different vegetation succession stages, the smallest ET is from cropland ( Zea mays + Brassica napus ), mainly result from that the planting density of Zea mays is smaller than that of grass to ensure high yield, and Brassica napus with high LAI grows in winter when PET is low (Figure S4 in Supporting Information ). While the secondary forest has the highest ET among all vegetation types, due to the large canopy and water uptake from the deep fractured bedrock (J. Y. Hu et al., 2021; Yang et al., 2014; Zeng et al., 2021). These variations of ET among vegetation types suggest that natural vegetation restoration increases ecosystem ET in the humid karst region, which is also similar to the findings in other non‐karst regions (Liu et al., 2013; Rohatyn et al., 2018; Twine et al., 2004; Zhang et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Tiemuerbieke et al (2018) found that desert shrubs adapted their root systems in response to changes in soil water, which is one of the most important strategies for adapting to periodic water shortages. Zeng et al (2021) pointed out that typical shrubs in karst areas can transfer water from different sources during different times according to their dimorphic root systems. Ding et al (2018) found that Salix cupularis , Potentilla fruticosa , Rhododendron thymifolium , and Salix oritrepha change their water use strategies according to soil water content.…”
Section: Discussionmentioning
confidence: 99%
“…C. nepalensis is a non-legume nitrogen-fixing plant that forms root nodules with the actinomycete Frankia 2 , 3 . The biological ability of nitrogen-fixation in this species contributes to its rehabilitation capacity of nutrient-poor degraded land 4 , 5 ; in combination with its osmotic adjustment function and drought tolerance 6 , 7 , C. nepalensis improves the abiotic conditions and provides more suitable habitat for associated plant species 8 10 . Furthermore, essential oils and extracts from C. nepalensis could be used as promising drugs due to their antimicrobial 11 , 12 and anti-convulsant activities 13 .…”
Section: Background and Summarymentioning
confidence: 99%